Cobalt–citrate framework armored with graphene oxide exhibiting improved thermal stability and selectivity for biogas decarburization. Issue 2 (19th November 2014) - Shen, Yangcan; Li, Ziyin; Wang, Lihua; Ye, Yingxiang; Liu, Qing; Ma, Xiuling; Chen, Qianhuo; Zhang, Zhangjing; Xiang, Shengchang
Abstract : The first example of core–shell MOF–GO composites exhibits significantly improved thermal stability and CO2 /CH4 selectivity compared with their parent materials. Abstract : A series of metal–organic framework (UTSA-16)–graphene oxide composites was synthesized. These composites are the first reported examples of core–shell type metal–organic framework composites armored with graphene oxide film. The parent materials (UTSA-16 and graphene oxide) and the nanocomposites were characterized using XRD, SEM, TEM, TGA and gas adsorption. The composites showed a greatly improved thermal stability compared with their parent materials. The UTSA-16–GO19 composite has a CO2 /CH4 selectivity of 114.4, which is three times greater than that of UTSA-16 alone; of the previously reported metal–organic frameworks, only the polyamine-incorporated amine-MIL-101(Cr) has a higher CO2 /CH4 selectivity. These graphene oxide composites provide a new direction for practical high-performance metal–organic framework materials.